2011
DOI: 10.1111/j.1600-6143.2011.03451.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of PDL1 Expression on Nonhematopoietic Donor Cells in Acquired Tolerance to Vascularized Cardiac Allografts

Abstract: The PD1:PDL1 pathway is an essential negative costimulatory pathway that plays a key role in regulating the alloimune response. PDL1 is expressed not only on antigen-presenting cells (APCs) but also cardiac endothelium. In this study, we investigated the importance of PDL1 expression on donor cardiac allograft in acquired transplantation tolerance in a fully MHC-mismatched model. We generated PDL1 chimeric mice on B6 background that expressed PDL1 on either hematopoietic cells or nonhematopoietic cells of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 23 publications
2
61
0
Order By: Relevance
“…In previous studies, PD-L1 chimeric mice that expressed PD-L1 only on hematopoietic cells of the heart showed an accelerated, early graft rejection after heart transplantation, whereas the expression of PD-L1 on non-hematopoietic cells of the heart led to a delayed rejection. These data indicate that PD-L1 expression on nonhematopoietic cells plays a significant role in regulating transplantation immune responses [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, PD-L1 chimeric mice that expressed PD-L1 only on hematopoietic cells of the heart showed an accelerated, early graft rejection after heart transplantation, whereas the expression of PD-L1 on non-hematopoietic cells of the heart led to a delayed rejection. These data indicate that PD-L1 expression on nonhematopoietic cells plays a significant role in regulating transplantation immune responses [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Donor tissue expression of PD-L1 provides protection against host T cell responses in cardiac and kidney allografts (34)(35)(36). More recently, Saha et al (15) reported that PD-L1 expression in host tissues played an important role in the suppression of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, Wang et al determined that the inhibition of mTOR reduces the ability of EC to interact with effector T cells and is associated with reduced T cell recruitment [56]. Thus, intracellular signals, molecular events and/or soluble factors regulate the immunogenicity of EC and have potential to shape the intragraft microenvironment to promote local immunoregulation and sustain alloimmune tolerance [65]. …”
Section: Immunogenic Function Of Microvascular Endothelial Cells As Amentioning
confidence: 99%